Accounting for the Human Factor. - Flamholtz, Eric G.; Moriarty, Shane R. (The Accounting Review, 1990)
Abstract Reviews the book `Accounting for the Human Factor,' by Lee D. Parker, Kenneth R. Ferris and David T. Otley.